Mercado de trabalho e turismo: emprego, renda e desenvolvimento socioeconômico no Ceará - Pereira Junior, José Silva (2010)
In Brazil and, especially, North-eastern, the sector of the tourism presents a dynamics characterized for an important impact of participation in the economy. In this context of economic evolution of the activity, it can be observed that another model has been argued and analyzed widely in the search of another possibility of the economic production that is capable to promote qualitative improvements through the productive activity, generating development and sustentability. As development instrument, the tourist activity needs to configure in process that aims, at beyond the dynamism and economic growth, the direct improvement of the quality of life of the population in inserted it. This quality of life and valuation can be gotten through the generation of jobs and income that truily value its beneficiary right-handers and that its results add real quality. Thus, with this perspective of understanding the relations of generated work and income in the interior of the tourist activity, the inherent quality and the real generated development that this research is presented, desiring to fill a gap in the target of the analyses of the work market of the sector of the tourism, its relations with the space and dynamism and decurrent improvement of it. This aim showed an adverse economic context to the development. The founded economic scene in the state of the Ceará related to on activities to the Tourism points that the desired social and economic development comes being relegated the inferior conditions to the economic growth, therefore the workers, probable first beneficiaries of the impacts generated for the sector, did not feel these increases, therefore its purchasing power and of consequent improvement of life did not follow the increases lived deeply for the sector.